Barriers for Quality Management Implementation in Higher Education - Dzingirai, Mufaro (IGI Global, 2021)
To survive in a highly-competitive higher education sector, institutions of higher learning are focusing on quality management principles. Therefore, a strong need emerges for a deeper understanding of quality management. Despite a substantial, growing interest from scholars, policymakers, and educationalists in quality management as a common phenomenon in higher education, many obstacles remain in the implementation process. This chapter captures the worldwide quality issues and a controversy related to implementation of quality management in higher education, identifies the barriers for successful implementation of quality management in higher education, reviews the key barriers that deter the efforts to effectively execute quality management in higher education so that quality management strategies can be formulated by the top management and policymakers accordingly, and presents directions for future research.